Impact of habitat loss and fragmentation on reproduction, dispersal and species persistence for an endangered Chilean tree - Lander, T; Harris, S; Cremona, P; Boshier, D (Springer Nature, 2019)
Survival of rare and endangered plant species following habitat loss and fragmentation is dependent upon in situ reproduction and population persistence, and establishment in new sites, so that stochastic, local extirpation does not lead to species extinction. Here we investigate if and how vegetative and sexual reproduction, propagule dispersal, and seedling establishment promote in situ persistence and establishment in new sites for the endangered, endemic Chilean tree Gomortega keule, in a landscape experiencing extensive habitat loss and fragmentation. Genetic analyses show G. keule reproduces vegetatively, producing large clone groups and providing a mechanism for long-term in situ persistence. Abundant seed set was observed, but seedling establishment was rare. At the single site where seedlings were observed, parentage analysis revealed seed dispersal over greater distances, and in a more aggregated pattern, than would be expected from gravity dispersal alone. We hypothesize that G. keule may represent a ‘seed dispersal anachronism’, wherein the native seed disperser has been lost and possibly replaced by domesticated cattle. The lack of seedling establishment at most sites raises concerns about the ability of existing populations to expand within existing habitat patches or establish at new locations. Globally, habitat loss and fragmentation, coupled with other environmental changes, pose a particular threat to rare species with small populations, because inbreeding and the loss of mutualists can lead to establishment failure and local extirpation. We propose that analysis of a plant’s reproductive strategies as a whole, in its landscape context, is essential for effective species conservation.